Quantum phases of hard-core bosons in a frustrated honeycomb lattice - C N Varney; K Sun; V Galitski; M Rigol (New Journal of Physics, 2012)
Using exact diagonalization calculations, we investigate the ground-state phase diagram of the hard-core Bose–Hubbard–Haldane model on the honeycomb lattice. This allows us to probe the stability of the Bose-metal phase proposed in Varney et al (2011 Phys. Rev. Lett. 107 077201), against various changes in the originally studied Hamiltonian.